2012
DOI: 10.1515/jpm-2012-0196
|View full text |Cite
|
Sign up to set email alerts
|

Presence of human milk bank is associated with elevated rate of exclusive breastfeeding in VLBW infants

Abstract: Human milk confers health benefits of vital importance for the sick and preterm infants in neonatal intensive care units (NICUs). Mother's own milk is the first choice in preterm infant feeding, and every effort should be made to promote lactation. When mother's milk is not available or is insufficient, donor human milk (DHM) is recommended. Yet, occasionally, the concern that the use of DHM might decrease breastfeeding is being raised. The present data collection planned by the Italian Association of Human Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 8 publications
4
81
0
10
Order By: Relevance
“…12 There has been debate about whether access to DHM could lead to decreased breastfeeding, the idea being that the availability of an alternate human milk source could lead to attenuated efforts to promote lactation among mothers of preterm infants. 13 A study by the Italian Association of Human Milk Banks showed that access to DHM was actually associated with an increased rate of exclusive breastfeeding in VLBW infants, 13 but data from US NICUs have been lacking. Data from human milk banks in the United States are not standardized, and there is a lack of a central depository.…”
Section: What This Study Addsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 There has been debate about whether access to DHM could lead to decreased breastfeeding, the idea being that the availability of an alternate human milk source could lead to attenuated efforts to promote lactation among mothers of preterm infants. 13 A study by the Italian Association of Human Milk Banks showed that access to DHM was actually associated with an increased rate of exclusive breastfeeding in VLBW infants, 13 but data from US NICUs have been lacking. Data from human milk banks in the United States are not standardized, and there is a lack of a central depository.…”
Section: What This Study Addsmentioning
confidence: 99%
“…A study of 83 NICUs in Italy found that breastfeeding at discharge tended to be higher in NICUs that had DHM available to them (60.4% vs 52.8%). 13 A single-center study conducted in the Connecticut Children's Medical Center's level-4 NICU that examined data from 154 infants found that the introduction of a DHM policy was associated with a significant increase in the proportion of human milk in the infants' diet. 16 A systematic review and metaanalysis conducted in 2003 based on 4 small trials that are now >30 years old found that infants who received DHM were 3 times less likely to develop NEC than infants who received formula.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The main reason probably, is that the early parenteral and, or enteral administration of large amounts of macronutrients and energy is still considered by many neonatologists to be insecure [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Certainly the initial concern that providing donor milk in the NICU would reduce rates of breastfeeding has been debunked. 1,7 However, it is widely appreciated that initiating and sustaining lactation remains a great challenge to mothers of VLBW infants. A systematic review identifying effective methods of breastfeeding promotion in NICUs offers food for thought: skin-to-skin…”
mentioning
confidence: 99%